1998
DOI: 10.1038/34178
|View full text |Cite
|
Sign up to set email alerts
|

The peroxisome proliferator-activated receptor-γ is a negative regulator of macrophage activation

Abstract: The peroxisome proliferator-activated receptor-gamma (PPAR-gamma) is a member of the nuclear receptor superfamily of ligand-dependent transcription factors that is predominantly expressed in adipose tissue, adrenal gland and spleen. PPAR-gamma has been demonstrated to regulate adipocyte differentiation and glucose homeostasis in response to several structurally distinct compounds, including thiazolidinediones and fibrates. Naturally occurring compounds such as fatty acids and the prostaglandin D2 metabolite 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

103
2,637
18
48

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,355 publications
(2,834 citation statements)
references
References 23 publications
103
2,637
18
48
Order By: Relevance
“…38 Carbon monoxide, a main product of heme oxygenase-1-mediated heme degradation, induces the expression of the transcription factor PPARg in macrophages 39 that drives antiinflammatory activation in macrophages and promotes adipogenesis and adipocyte function. 40,41 Thus, heme oxygenase-1 has a putative beneficial function in adipose tissue through antioxidative, metabolic and anti-inflammatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…38 Carbon monoxide, a main product of heme oxygenase-1-mediated heme degradation, induces the expression of the transcription factor PPARg in macrophages 39 that drives antiinflammatory activation in macrophages and promotes adipogenesis and adipocyte function. 40,41 Thus, heme oxygenase-1 has a putative beneficial function in adipose tissue through antioxidative, metabolic and anti-inflammatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR␥ has recently been suggested to function as a negative regulator of inflammatory responses. PPAR␥ ligands are capable of reducing the expression of genes for cytokines (e.g., TNF␣, IL-6, and IL-1␤), iNOS, gelatinase B, scavenger receptor A, and COX-2 in activated macrophages (9,10,26).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that PPAR␥ has diverse effects on a wide variety of cells and plays a crucial role in the regulation of monocyte differentiation, atherosclerosis, immune responses, apoptosis, and carcinogenesis (8). Of particular interest is the possibility that it may exert an antiinflammatory effect by inhibiting the gene expression of proinflammatory cytokines, inducible nitric oxide synthase (iNOS), proteinases, and cyclooxygenase (COX) (9,10). In order to elucidate the regulatory mechanisms that cause acute gout to resolve, we conducted experiments investigating the expression of PPAR␥ by MSU crystal-stimulated monocytes and the therapeutic effect of PPAR␥ ligands on crystal-induced acute inflammation.…”
mentioning
confidence: 99%
“…To establish that IL-13 regulates CD36 expression through PPARc, we performed transfection experiments on the murine Mu cell line RAW264.7, which expresses very low levels of PPARc mRNA [25]. IL-13 and rosiglitazone did not induce an increase in CD36 expression in this cell line transiently transfected with a control plasmid (RSV-bGal) (Fig.…”
Section: Il-13 Regulates Cd36 Expression Through Pparcmentioning
confidence: 99%